Calcium and Signal Transduction 2018
DOI: 10.5772/intechopen.78587
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Calcium Signaling by STIM1 and ORAI1

Abstract: STIM1 and ORAI1 proteins are regulators of intracellular Ca 2+ mobilization. This Ca 2+ mobilization is essential to shape Ca 2+ signaling in eukaryotic cells. STIM1 is a transmembrane protein located at the endoplasmic reticulum, where it acts as an intraluminal Ca 2+ sensor. The transient drop of intraluminal Ca 2+ concentration triggers STIM1 activation, which relocates to plasma membrane-endoplasmic reticulum junctions to bind and activate ORAI1, a plasma membrane Ca 2+ channel. Thus, the Ca 2+ influx path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, Mapk14 expression was significantly upregulated in Stim1 deficient ameloblasts. MAPK14 has been shown to regulate SOCE both indirectly (through TGF-β1 and NF-kappa) or directly by phosphorylating Stim1 (Martin-Romero et al, 2018). In ameloblasts, MAPK14 has been shown to play a role in regulating early tooth morphogenesis and its ectodermal tissue deletion results in abnormally shaped dental cusps and a profoundly hypoplastic enamel layer (Greenblatt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Mapk14 expression was significantly upregulated in Stim1 deficient ameloblasts. MAPK14 has been shown to regulate SOCE both indirectly (through TGF-β1 and NF-kappa) or directly by phosphorylating Stim1 (Martin-Romero et al, 2018). In ameloblasts, MAPK14 has been shown to play a role in regulating early tooth morphogenesis and its ectodermal tissue deletion results in abnormally shaped dental cusps and a profoundly hypoplastic enamel layer (Greenblatt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated CREB translocates into the nucleus where it recognizes the CRE of the Per genes promoters and induces their expression ( Lee et al, 2010 ). Furthermore, it has been shown that SOCE is essential for activating CREB in multiple tissues including smooth muscles and immune cells ( Avila-Medina et al, 2018 ; Martin-Romero et al, 2018 ). The fact that SOCE-deficient ameloblast showed significantly lowered levels of the Per 2 genes suggests that control of CREB activity may represent one of the main mechanisms by which SOCE can directly affect the circadian TTFLs in ameloblasts, similar to the SCN and other cells ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oligomers of active STIM1 are less mobile and phospho-STIM1 is found at the cell periphery[10], close to the plasma membrane, where it binds ORAI1. Because STIM1 and ORAI1 are ubiquitous, they are involved in a wide range of signaling pathways that regulate many cellular functions[11]. However, the number of studies about the role of STIM1 in neuronal tissue is much more limited.…”
Section: Stim1 and Calcium Mobilizationmentioning
confidence: 99%
“…Consequently, Ca 2+ influx through STIM1-regulated channels is referred to as store-operated Ca 2+ entry (SOCE). This influx of extracellular Ca 2+ modulates numerous cellular events, such as cortical cytoskeleton reorganization, cell migration, the cell cycle, and the regulation of gene expression [reviewed in ( 9 )]. This extensive regulation is attributed to the numerous Ca 2+ -dependent signaling pathways that rely on STIM1/ORAI1.…”
Section: Introductionmentioning
confidence: 99%